30th AIAA Applied Aerodynamics Conference 2012
DOI: 10.2514/6.2012-2795
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamics of a Swept Wing with Ice Accretion at Low Reynolds Number

Abstract: This paper discusses the use of several experimental techniques to investigate the performance and flowfield of a swept wing with leading-edge ice at low Reynolds numbers. Force balance measurements were made over a range of angles of attack and Reynolds numbers. Surface oil visualization and pressure sensitive paint were used to investigate the flow over the surface of the wing, while five-hole probe wake surveys were used to investigate the wake. The flowfield of the iced swept wing was dominated by a leadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(42 citation statements)
references
References 16 publications
3
39
0
Order By: Relevance
“…The results indicate that, for a fixed CL, the ice shape results in a significant increase in the profile drag, whereas the induced drag is unaffected. In the surface oilfiow, not shown here, it was observed that the size of the region of separated flow, relative to the local chord, increased as the tip was approached [6,15]. The flow visualizations of Diebold and Bragg [15] and Diebold et al [6] showed a leading-edge vortex behind the ice shape that grows with angle o f attack.…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…The results indicate that, for a fixed CL, the ice shape results in a significant increase in the profile drag, whereas the induced drag is unaffected. In the surface oilfiow, not shown here, it was observed that the size of the region of separated flow, relative to the local chord, increased as the tip was approached [6,15]. The flow visualizations of Diebold and Bragg [15] and Diebold et al [6] showed a leading-edge vortex behind the ice shape that grows with angle o f attack.…”
Section: Resultsmentioning
confidence: 54%
“…Maskell [12] refined the work of Betz [11] by introducing the blockage velocity ub, which acts as a small correction for the effect of tunnel walls on the velocity. Detailed derivations can be found in numerous references [7][8][9]13], For this work, a semispan wing model was constructed and tested in the 2.8-by-4-ft low-speed wind tunnel at the University of Illinois. (2) and (3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 6 shows some details of the IM swept wing geometry. The wing is fully described in [10]. The following §ow parameter values were used: angle of attack 0 • , free-stream air pressure 10 5 Pa, and free-stream air velocity 49.1 m/s.…”
Section: Three-dimensional Ice Accretions Forming On Illinois Model Smentioning
confidence: 99%
“…The Illinois Model (IM) swept wing has been considered. It is a version of the Common Research Model (CRM) and is fully described in [10]. The FLOWer code was chosen because of potential extension of our capabilities to other larger wings or faster §ight speeds.…”
Section: Computational Fluid Dynamics Solversmentioning
confidence: 99%